The wheat NB‐LRR gene TaRCR1 is required for host defence response to the necrotrophic fungal pathogen Rhizoctonia cerealis. Issue 6 (1st March 2017) - Zhu, Xiuliang; Lu, Chungui; Du, Lipu; Ye, Xingguo; Liu, Xin; Coules, Anne; Zhang, Zengyan
Summary: The necrotrophic fungus Rhizoctonia cerealis is the major pathogen causing sharp eyespot disease in wheat ( Triticum aestivum ). Nucleotide‐binding leucine‐rich repeat (NB‐LRR) proteins often mediate plant disease resistance to biotrophic pathogens. Little is known about the role of NB‐LRR genes involved in wheat response to R. cerealis . In this study, a wheat NB‐LRR gene, named TaRCR1, was identified in response to R. cerealis infection using Artificial Neural Network analysis based on comparative transcriptomics and its defence role was characterized. The transcriptional level of TaRCR1 was enhanced after R. cerealis inoculation and associated with the resistance level of wheat. TaRCR1 was located on wheat chromosome 3BS and encoded an NB‐LRR protein that was consisting of a coiled‐coil domain, an NB‐ARC domain and 13 imperfect leucine‐rich repeats. TaRCR1 was localized in both the cytoplasm and the nucleus. Silencing of TaRCR1 impaired wheat resistance to R. cerealis, whereas TaRCR1 overexpression significantly increased the resistance in transgenic wheat. TaRCR1 regulated certain reactive oxygen species (ROS)‐scavenging and production, and defence‐related genes, and peroxidase activity. Furthermore, H2 O2 pretreatment for 12‐h elevated expression levels of TaRCR1 and the above defence‐related genes, whereas treatment with a peroxidase inhibitor for 12 h reduced the resistance of TaRCR1‐ overexpressing transgenic plants and expression levels of these defence‐related genes. Taken together, TaRCR1 positively contributes to defence response to R. cerealis through maintaining ROS homoeostasis and regulating the expression of defence‐related genes.